Correlation between aerobic and anaerobic resistance to metronidazole in trichomonads: application of a new computer program for permutation tests - Flegr, J; Záboj, P; Vanácová, S (Parasitology research, 1998)
An indispensable step of any comparative study is testing the concordance between the distribution of phenetic traits and the evolutionary history of the taxa under study. Here we present a computer program TREEPT which can perform these tasks on the basis of a permutation test. The use of the program was demonstrated on trichomonad drug sensitivity data. The program can also perform permutation tests analogous to the t-test, analysis of variance (ANOVA) and correlation analysis and is available at http://www.natur.cuni.cz/flegr/PROGRAMS/+ ++TREEPT.ZIP and http://www.karlin. mff.cuni.cz/-zaboj/treept.
Keywords: Drug Resistance; Analysis of Variance; fylogeneze; Phylogeny; anaerobióza; Metronidazole; Software; léková rezistence; Antitrichomonal Agents; Trichomonas vaginalis; Animals; analýza rozptylu; metronidazol; Aerobiosis; zvířata; antitrichomonádové látky; Anaerobiosis; software; aerobióza